Clinical added value of magnetic source imaging in the presurgical evaluation of refractory focal epilepsy. Issue 4 (19th January 2012) - De Tiège, Xavier; Carrette, Evelien; Legros, Benjamin; Vonck, Kristl; Op de beeck, Marc; Bourguignon, Mathieu; Massager, Nicolas; David, Philippe; Van Roost, Dirk; Meurs, Alfred; Lapere, Samuel; Deblaere, Karel; et al.
Abstract : Objective: This prospective, bicentre, blinded, intention to treat study assessed the clinical added value of magnetic source imaging (MSI) in the presurgical evaluation of patients with refractory focal epilepsy (RFE). Methods: 70 consecutive patients with RFE (42 men; mean age 31.5 years, range 3–63) from two Belgian centres were prospectively included. All patients underwent conventional non-invasive presurgical evaluation (CNIPE) and a whole head magnetoencephalography recording (Elekta Neuromag). Equivalent current dipoles corresponding to interictal epileptiform discharges (IED) were fitted in the patients' spherical head model and coregistered on their MRI to produce MSI results. Results of CNIPE were first discussed blinded to the MSI results in respective multidisciplinary epilepsy surgery meetings to determine the presumed localisation of the epileptogenic zone and to set surgical or additional presurgical plans. MSI results were then discussed multidisciplinarily. MSI influence on the initial management plan was assessed. Results: Based on CNIPE, 21 patients had presumed extratemporal epilepsy, 38 had presumed temporal epilepsy and 11 had undetermined localisation epilepsy. MSI showed IED in 52 patients (74.5%) and changed the initial management in 15 patients (21%). MSI related changes were significantly more frequent in patients with presumed extratemporal or undetermined localisation epilepsy compared with patients with presumed temporal epilepsy (p≤0.001). These changes had a clear impact on clinical management in 13% of all patients. Conclusion: MSI is a clinically relevant, non-invasive neuroimaging technique for the presurgical evaluation of patients with refractory focal epilepsy and, particularly, in patients with presumed extratemporal and undetermined localisation epilepsy.